ANALISIS MUTU KIMIA DAN SENSORIS TERASI UDANG DI DESA KAUKAU, KEPULAUAN SELAYAR. - Umniyah Musdhalifah Yusran; Dian Purnamasari Anwar; Citra Amelya Rosenari (Universitas Mataram, 2026)
The shrimp paste produced in Kaukau Village is widely marketed, indicating a high level of consumer acceptance. However, scientific information regarding the chemical and sensory quality profile of shrimp paste produced in Kaukau Village remains limited. This study aimed to analyze the chemical and sensory quality of shrimp paste processed using two different processing methods, namely a grinder and a traditional pounding tool. Purposive sampling was applied to collect shrimp paste samples from local producers. Sensory evaluation was conducted by 30 panelists assessing appearance, color, odor, taste, and texture. Chemical analyses included determination of moisture content, protein content, acid-insoluble ash, and salt content. The data were analyzed descriptively and presented in tables and figures. The sensory evaluation results indicated that shrimp paste produced using both processing methods exhibited good sensory quality, with appearance scores of 7.4–8.8, odor scores of 6.8–7.2, taste scores of 6.8–7.2, and texture scores of 6.8. The chemical composition of shrimp paste from both processing methods showed moisture contents of 24.53–25.05%, protein contents of 63.36–63.38%, acid-insoluble ash contents of 0.58–1.35%, and salt contents of 0.58–0.75%. In conclusion, shrimp paste processed using a grinder and a traditional pounding tool exhibited relatively similar chemical and sensory qualities, except for acid-insoluble ash content, which tended to be higher in shrimp paste processed using the traditional pounding method.